Numerical Study On Characteristics Of The Backward-Facing Step Flow With Variations Of The Slope Angle Of The Step - julian, james; Anggara, Rizki Aldi; Wahyuni, Fitri (Politeknik Negeri Lhokseumawe, 2024)
The phenomenon of flow separation plays a vital role in the industrial world. The backward-facing step (BFS) is a general form representing flow separation. This study investigates the influence of the slope angle of the step on BFS flow characteristics at various low Reynolds numbers. According to the CFD results, the flow separation phenomenon forms a circulation zone for each increase in Reynolds numbers. This phenomenon is a result of the sudden expansion of the channel geometry. The BFS with the slope angle of the step demonstrates that the increase in the recirculation zone can be minimized, thus appropriately delaying flow separation. The recirculation zone causes fluid flow to reverse direction, affecting fluid flow efficiency due to resulting pressure differences. Therefore, a BFS with the slope angle of the step exhibits a more efficient flow phenomenon by minimizing the recirculation zone.